If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 6x = -60 Solving 6 + 6x = -60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = -60 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = -60 + -6 6x = -60 + -6 Combine like terms: -60 + -6 = -66 6x = -66 Divide each side by '6'. x = -11 Simplifying x = -11
| 1.25g=15g+.50 | | y=2(1)+2.50(1) | | -4+7x=-46 | | 4+8=8+x | | 12x^2+-8x+1=0 | | n+6.92=11.77 | | -7-3x=29 | | 14.75g=.50 | | (2x+10)(3x-1)=150 | | 3p+45=68 | | 1.5-2= | | (5w-1)(5+w)=0 | | (2x-3)+1=17 | | 3.5+-9= | | -3(1-4n)=-63 | | y=2*4+2.50*4 | | (7+4w)=13 | | -26+7p=5(3p+6) | | -3(1-4n)=63 | | -3(1-4)=-63 | | 1.5-7= | | y=2(2)+2.50(2) | | 3b+-4=14 | | -15a-a+4=64 | | -21n-15=-82 | | -13a-18=73 | | 21x-28= | | h=-16t^2+16t+112 | | -3(x-1)+8(x-3)=6x-5x | | -5k-7=-37 | | p/2=3/4+p/3 | | x=9x^3-6x^2 |